Pemanfaatan Media Pembelajaran Geografi Berbantuan Quizizz sebagai Strategi Pembelajaran Masa Pendemi Covid-19 pada Peserta Didik Kelas XII IPS 5 Semester 2 SMA Negeri 3 Purwokerto Tahun Pelajaran 2020/2021 - Wahyuliani (Proceedings Series on Social Sciences & Humanities, 2021)
In line with the expectations of the government, parents and the public on the quality of Indonesian education both academic and non-academic, namely the character of students, it is necessary to creativity and innovation of teachers in teaching and learning activities in the midst of the Covid-19 pandemic. Geography subjects are subjects of interest that are mandatory and important for ips majors, so it should be students majoring in IPS master the lessons that are characteristic of the department, while some students say the geography of boring material let alone learning in the era of Covid-19 protesters where teachers do not come face to face with students. These things that cause low learning outcomes because boredom has an impact on the lack of interest and yearly curiosity in the material delivered by the teacher. The teacher's strategy in addressing the problem is to make use of quizizz-assisted geography learning media. The purpose of writing this paper is to describe the use of geography learning media assisted by quizizz as a learning strategy for the Covid-19 protesters in students of Class XII IPS 5 Semester 2 SMA N 3 Purwokerto Year 2020/2021. The use of geography-assisted learning media quizizz can improve the learning outcomes and the spirit of student competition on remote sensing materials. Evalution results after learning is the percentage of completion of learners 89.7 % and has exceeded 75% of the number of learners so that the learning is declared effective.